Total Factor Productivity and the R & D Expenditures - Anton Abdulbasah Kamil (STATISTIKA: Forum Teori dan Aplikasi Statistika, 2009)
The total factor productivity (TFP) growth comes from improvements in the quality of labor and capitaland from other sources of technological change, many of them in the form of externalities, spillovers,representing contributions of science and innovations in other enterprises, industries and countries.Economies of scale and scope, as well as improving x-efficiency, are among the other potentialsources of total factor productivity growth. The goal of this paper is to advance the debate on thecontribution of R & D to productivity. We used the method of constructing a proxy variable for interindustrytechnology spillovers and test its statistical association with the TFP growth.